Simulasi Model Matematika Dispersi Larutan Limbah Pada Saluran Air - LELEURY, ZETH ARTHUR; TOMASOUW, BERNY PEBO (Universitas Islam Madura, 2019)
Water pollution is now a condition that needs special attention. One source of water pollution comes from waste solutions that produce pollutants that can reduce water quality. The Chemical Oxygen Demand (COD) number is a parameter used to measure waste pollution. The purpose of this research is to examine the effect of flow velocity and rate of change of substances on COD concentrations. The method used in this research is a finite difference method to express the discrete form of a mathematical model of the dispersion of a waste solution in a water channel. The results show that the greater the flow velocity, the lower the COD concentration and the greater the rate of change in the concentration of substances, the higher the COD concentration. So if the COD is high then the water quality is not good to use or in other words the water can be said to be polluted.